The Security Implications of BREXIT - Zendelovski, Goran; Pavleski, Aleksandar (Филозофски факултет, Скопје, 2018)
Over the past decade, the European Union has faced numerous turmoil and crises that directly affected its stability and prosperity. Starting with conflicts in Africa, economic crises, uncertainty about partnerships and enlargement, the stability of the Western Balkan countries, terrorist attacks in European cities, to migration and refugee crises. These complex events led to tensions and divisions within the Union, the rise of populist anti-EU parties, and culminated with the decision of the UK to leave the EU. In recent years, Europe has been one of the most developed forms of regional integration on a political, economic and security plan, but the events around Brexit have undermined the unity and the existence of the Union. This historic precedent can have a domino effect on the other EU member states and change the direction of the states towards European security and defense. The paper will analyze the losses and benefits of the United Kingdom from the membership in the Union, as well as the current and future relations of Britain with Europe and the world and the possible implications for the EU's foreign and security policy
Keywords: EU, BREXIT, INTEGRATION, DISINTEGRATION, SECURITY IMPLICATIONS.